2012
DOI: 10.1103/physrevb.86.035142
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous work function anisotropy in ternary acetylides

Abstract: Anomalous anisotropy of workfunction values in ternary alkali metal transition metal acetylides is reported. Workfunction values of some characteristic surfaces in these emerging semiconducting materials may differ by more than ≈ 2 eV as predicted by Density Functional Theory calculations. This large anisotropy is a consequence of the relative orientation of rod-like [MC2]∞ negatively charged polymeric subunits and the surfaces, with M being a transition metal or metalloid element and C2 refers to the acetylid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The latter are semiconductors with small indirect band gaps, whose sizes depend on the nature of the respective alkali metal ion A + . Very recently, these compounds have attracted some attention, as based on DFT calculations it was concluded that they should exhibit an anomalous anisotropy of workfunction values making them interesting candidates for possible applications as photocathodes and novel intercalation electrode materials for batteries . Even better workfunction values were calculated for a potential Cs 2 TeC 2 compound, which was assumed to crystallize in the Na 2 PdC 2 structure type with linear ⋅⋅⋅Te‐C≡C‐Te⋅⋅⋅ chains in these calculations .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The latter are semiconductors with small indirect band gaps, whose sizes depend on the nature of the respective alkali metal ion A + . Very recently, these compounds have attracted some attention, as based on DFT calculations it was concluded that they should exhibit an anomalous anisotropy of workfunction values making them interesting candidates for possible applications as photocathodes and novel intercalation electrode materials for batteries . Even better workfunction values were calculated for a potential Cs 2 TeC 2 compound, which was assumed to crystallize in the Na 2 PdC 2 structure type with linear ⋅⋅⋅Te‐C≡C‐Te⋅⋅⋅ chains in these calculations .…”
Section: Figurementioning
confidence: 99%
“…Very recently, these compounds have attracted some attention, as based on DFT calculations it was concluded that they should exhibit an anomalous anisotropy of workfunction values making them interesting candidates for possible applications as photocathodes and novel intercalation electrode materials for batteries . Even better workfunction values were calculated for a potential Cs 2 TeC 2 compound, which was assumed to crystallize in the Na 2 PdC 2 structure type with linear ⋅⋅⋅Te‐C≡C‐Te⋅⋅⋅ chains in these calculations . Although the assumption of Te 0 with a linear coordination is not in agreement with the expected coordination geometry, it was the same group that claimed in a recent work the successful synthesis and structural elucidation of Li 2 TeC 2 crystallizing in the Na 2 PdC 2 structure type as well as Na 2 TeC 2 , crystallizing in a different structure, but also exhibiting linear ⋅⋅⋅Te‐C≡C‐Te⋅⋅⋅ chains .…”
Section: Figurementioning
confidence: 99%
“…However, due to its explosivity when heated to 240 o C, or due to mechanical impact or electrical ark 12 its application is rendered unsafe in batteries. Conjugated 1D polymers occur in many other materials, especially in coordination polymers, such as CuCN, AgCN, AuCN or ternary acetylides 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrathin oxide monolayers over metal surfaces change the electrostatic boundary conditions on the surface and thus they may significantly decrease or increase the workfunctions and the shape and occupation of surface bands which leads to drastic changes in the properties of the emitted electrons . In the second example, we have pointed out that the workfunction of the seasoned, high quantum efficiency Cs 2 Te photoemissive material can be lowered from ≈3 eV to about 2.4 eV by acetylation resulting in Cs 2 TeC 2 , whereas its quantum efficiency is preserved . Analogous compounds Cs 2 PdC 2 and Cs 2 PtC 2 exist and we have managed to synthesize Li 2 TeC 2 (X‐ray diffraction confirms theoretically predicted structure; K. Németh et al, to be published) as the first member of ternary acetylides with Te.…”
Section: Resultsmentioning
confidence: 99%